(untitled) (World of finance, 2023)
Introduction. The peculiarities of insurance marketing are determined, on the one hand, by the nature of the insurance service, and on the other, by the specifics of the insurance market. In modern conditions, the role of insurance marketing in the activities of insurance companies is growing, which is connected with the change in lifestyle and the risks that arise, increased competition in the insurance market, the development of digital technologies, and the growing awareness of the need and role of insurance in protection against risks. Therefore, a necessary condition for the successful operation of any insurance company in a competitive environment is the development of an effective marketing strategy that makes it possible to attract new customers, retain existing ones and increase profitability, as well as develop the brand and positive image of the insurer. The purpose of the article is to determinate the main areas of improvement of insurance marketing in Ukraine through the analysis of key factors affecting the quality of marketing policy in the context of the provision of insurance services. Results. The article identifies the main factors influencing the rapid development of insurance marketing. Based on a retrospective analysis, the main stages of the formation of insurance marketing (from the beginning of the 60s of the 20th century to the present) are considered. The key elements of the insurance marketing complex are identified, based on the theoretical and methodological principles of the functioning of marketing as an economic process. In order to deepen the understanding of the concept of insurance marketing, the existing approaches to defining the concept of "insurance marketing" were considered. Classification of influencing factors on consumer behavior in the context of insurance marketing is proposed. The peculiarities of insurance marketing are analyzed and the main aspects of the implementation of an effective insurance marketing strategy are summarized, taking into account international experience. Conclusions. Insurance marketing in Ukraine is becoming an increasingly important component of the success of insurance companies, especially in the conditions of growing competition in the market of insurance services. Accordingly, insurance companies in Ukraine actively use various marketing strategies to attract and retain customers, increase profits and promote the brand The main areas of improvement of insurance marketing in Ukraine are: use of digital communication channels, such as social networks and other online channels; personalized insurance products and services that meet the individual needs of clients; development of innovative insurance products and services; improving the quality of service and transparency of insurance services, which will allow insurance companies to increase the trust of clients in their services and ensure stable development in the market; use of artificial intelligence and data analytics.